Inoculation of tomato seedlings with Trichoderma Harzianum and Arbuscular Mycorrhizal Fungi and their effect on growth and control of wilt in tomato seedlings - Mwangi, Margaret W. (Sociedade Brasileira de Microbiologia, 2011)
A green house study was conducted to investigate the ability of an isolate of Trichoderma harzianum (P52) and arbuscular mycorrhizal fungi (AMF) in enhancing growth and control of a wilt pathogen caused by Fusarium oxysporum f. sp. lycopersici in tomato seedlings. The plants were grown in plastic pots filled with sterilized soils. There were four treatments applied as follows; P52, AMF, AMF + P52 and a control. A completely randomized design was used and growth measurements and disease assessment taken after 3, 6 and 9 weeks. Treatments that significantly (P < 0.05) enhanced heights and root dry weights were P52, AMF and a treatment with a combination of both P52 and AMF when compared the control. The treatment with both P52 and AMF significantly (P < 0.05) enhanced all growth parameters (heights; shoot and root dry weight) investigated compared to the control. Disease severity was generally lower in tomato plants grown with isolate P52 and AMF fungi either individually or when combined together, though the effect was not statistically significant (P≥ 0.05). A treatment combination of P52 + AMF had less trend of severity as compared to each individual fungus. T. harzianum and AMF can be used to enhance growth in tomato seedlings.